Dry anaerobic digestion of chicken manure coupled with membrane separation of ammonia - ÇALLI, BARIŞ (ELSEVIER SCI LTD, 2017)
In this study, the anaerobic digestion of egg-laying hen manure combined with membrane-based ammonia separation was investigated. Long-term continuous experiments with and without ammonia separation were performed by increasing the organic loading rate (OLR). Although the control digester was completely inhibited at an OLR and influent total Kjeldahl nitrogen (TKN) concentration of 3.85 kgVS/m(3).d and 8.2 g/l, respectively, an average methane yield of 0.30 +/- 0.02 m(3)/kgVS was achieved with a membrane-integrated digester at an OLR and influent TKN concentration of 6.0 kgVS/m(3).d and 15 g/l, respectively. When the ammonia concentration increased above 4000 mg/l, hydrogenotrophic methanogens Methanoculleus bourgensis and Methanobrevibacter sp. performed methane production via syntrophic acetate oxidation.
Keywords: Ammonia; Dry anaerobic digestion; Membrane separation; Chicken manure; BIOGAS PRODUCTION; CO-DIGESTION; POULTRY LITTER; AGRICULTURAL WASTES; METHANE PRODUCTION; GENOME SEQUENCE; SWINE MANURE; LOADING RATE; INHIBITION; REMOVAL